Rows with the neighbours: the short lives of longhouses at the Neolithic site of Versend-Gilencsa. (9th February 2018) - Jakucs, János; Oross, Krisztián; Bánffy, Eszter; Voicsek, Vanda; Dunbar, Elaine; Reimer, Paula; Bayliss, Alex; Marshall, Peter; Whittle, Alasdair
Abstract: Abstract : Longhouses are a key feature of Neolithic Linearbandkeramik (LBK) settlements in Central Europe, but debate persists concerning their usage, longevity and social significance. Excavations at Versend-Gilencsa in south-west Hungary ( c. 5200 cal BC) revealed clear rows of longhouses. New radiocarbon dates suggest that these houses experienced short lifespans. This paper produces a model for the chronology of Versend, and it considers the implications of the new date estimates for a fuller understanding of the layout and duration of LBK longhouse settlements.